The interaction between retirement and job search: a global approach to older workers employment - Jean-Olivier Hairault; François Langot; Thepthida Sopraseuth (Institute for the Study of Labor (IZA), 2006)
This paper presents a theoretical foundation and empirical evidence in favor of the view that the tax on continued activity not only decreases the participation rate by inducing early retirement, but also badly affects the employment rate of older workers just before early retirement age. Countries with an early retirement age at 60 also have lower employment rates for old workers aged 55-59. Based on the French Labor Force Survey, we show that the likelihood of employment is significantly affected by the distance from retirement, in addition to age and other relevant variables. We then extend McCall's (1970) job search model by explicitly integrating life-cycle features and retirement decisions. Using simulations, we show that the effective tax on continued activity caused by French social security system in conjunction with the generosity of unemployment benefits for older workers helps explain the low rate of employment just before the early retirement age. Decreasing this tax, thus bringing it closer to the actuarially-fair scheme, not only extends the retirement age, but also encourages a more intensive job-search by older unemployed workers.
Keywords: J22; J26; H31; 330; retirement; old workers; search; actuarial fairness